The complete nucleotide sequences of the cloned hepatitis B virus DNA; subtype adr and adw. - Ono, Y (1983)
The complete nucleotide sequences of two different subtypes (adr and adw) of hepatitis B virus (HBV) DNA cloned in E. coli were determined. The sequence of the viral genome of the adr clone was 3188 nucleotides long, and that of the adw clone was 3200 nucleotides long. The adr and adw clones differed from the reported cloned ayw HBV DNA (3182 nucleotides long) in 11.2% and 10.0% of nucleotides, respectively. Heterogeneity of the HBV genome in the clones with the same subtype was observed.